EFFECT OF CONCENTRATION EXTRACT BINAHONG (ANREDERA CORDIOFOLIA (TEN.) STEENIS) ON SENSORY QUALITY OF CHICKEN MEAT - A., Ioga; Okarini, I. A; Miwada, I N.S (Jurnal Peternakan Tropika, 2020)
This study aims to study how the different levels of concentrations of binahong (Anredera cordiofolia (Ten.) Steenis) leaf extracts as herbal additives in improving sensory quality of chicken meat. This study uses a 10 minute immersion in each treatment with a research design using a Completely Randomized Design (CRD) with 3 treatments and evaluated by 15 panelists as replications. The three treatments are: immersion of chicken meat without binahong leaf extract (K0), immersion in 10% binahong leaf extract (K10) and immersion in 50% binahong leaf extract (K50). Sensory quality variables observed included: color, aroma, taste, texture, tenderness and overall acceptance of chicken meat. The results showed that the concentration of binahong leaf extract could increase the panelists' preference for color, aroma, flavor, and overall acceptance of chicken meat, compared to control treatment. However, immersion treatment of binahong leaf extract with a concentration of 10 and 50% shows the results of the panelists' assessment of the same color (5.2 - 5.8 = like - rather like) and tenderness of meat (5.4 = somewhat like). The conclusion of the study that chicken meat immersion in binahong leaf extract can improve the sensory quality of meat in terms of color, aroma, flavor, and overall acceptance with the best soaking concentration is 50% concentration.   Keywords: Chicken meat, quality, binahong leaves.